Metabolism of glioblastoma: a review of metabolic adaptations and metabolic therapeutic interventions - Chung, James; Saad, Jawad; Kafri, Ahmad; Rossignol, Julien; Verbrugge, Maxwell; Bakke, Jesse (Frontiers in Oncology, 2025)
Glioblastoma (GBM) is the most common and aggressive primary malignancy of the central nervous system, marked by profound metabolic reprogramming that promotes growth, invasion, and therapeutic resistance. This review examines metabolic adaptations that sustain GBM progression and summarizes current and emerging strategies that target these pathways. GBM cells display increased aerobic glycolysis, glutaminolysis, lipid and cholesterol synthesis, and mitochondrial remodeling. These processes are regulated by oncogenic alterations such as EGFR amplification, PTEN loss, and HIF-1α stabilization, which allow tumor cells to thrive in hypoxic and nutrient-poor environments. Accumulation of lactate further supports metabolic flexibility and promotes an immunosuppressive microenvironment. Recent studies have focused on exploiting these metabolic vulnerabilities through dietary, pharmacologic, and oxygen-modulating interventions. The ketogenic diet has been explored as an adjuvant therapy to reduce glucose availability and enhance treatment sensitivity. Pharmacologic approaches include inhibition of key metabolic enzymes such as hexokinase 2, pyruvate kinase M2, pyruvate dehydrogenase kinase, and glutaminase. Additional strategies aim to disrupt mitochondrial function through VDAC1 blockade or to reduce tumor hypoxia using hypoxia-activated prodrugs, hyperbaric oxygen therapy, and oxygen-transporting agents. Preclinical findings suggest these approaches can suppress tumor proliferation and improve responsiveness to radiation and chemotherapy, although clinical evidence remains limited. Combining metabolic interventions with standard therapies may help overcome GBM’s intrinsic resistance and metabolic plasticity. Overall, the review highlights metabolism as a key determinant of GBM pathophysiology and a promising target for therapeutic innovation, emphasizing the importance of continued translational research to identify and exploit context-specific metabolic vulnerabilities in this highly lethal disease.